Nuclear data for neutron calculations of the reactors - Лещенко, Борис Юхимович; Бондар, Віра Михайлівна; Бондар, Борис Михайлович; Алізадех, Мохаммедалі (Eastern-European Journal of Enterprise Technologies, 2014)
Nuclear data on nuclear reaction cross sections with gammaquanta escape in the interaction of fast neutrons with the reactor structural materials are important for neutron-physical calculations of reactors. These data are necessary to estimate the gamma fields in the reactor core and calculate radiation protection. In addition, the study of nuclear reaction cross sections are needed to study different mechanisms of nuclear reactions and features of the excited states of nuclei and their decay. The results of studying nuclear data on nuclear reaction cross sections on cadmium in the energy range from 2 to 8 MeV are given in the paper. The values of cross sections are recovered from the corresponding amplitude instrument spectra, and their errors are estimated. The experimental results are compared with the results of theoretical calculations, performed within the framework of the statistical Hauser-Feshbach model, taking into account particle preequilibrium escape. The obtained results are included in the international experimental nuclear data library and can be used for neutron-physical calculations of reactors. The investigated theoretical models can be used for estimating nuclear data, which are missing in the international experimental nuclear data libraries.